:HEALTH, AGING, AND SOCIETY - Moremen, Robin (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The purpose of this course is to examine, from a sociological perspective, health and aging over the life course. We will analyze the way social factors influence health and aging at the individual, group, and societal levels. We will learn that the social aspects of health and aging are just as important as the physical and biological aspects, and that health and aging over the life span are influenced by the social, political, and economic environments in which individuals, groups, and societies are located. In the course of investigating the social aspects of health and aging, we will be reminded that systems of inequality, particularly those based on race, class, and gender, profoundly affect health and aging behaviors and outcomes.